READING CLAUDIO FROM MEASURE FOR MEASURE THROUGH FEMINISM - Dubey, Yogesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present paper attempts to examine the character of Shakespeare’s Claudio from Measure for Measure in the light of feminism. Though a number of studies have been conducted on the character of Claudio, his character from the feminist perspective still seems to have scope for further investigation. This paper undertakes to revisit the character of Claudio and expose his patriarchal character that looks at women only as secondary to men.